Psychosocial markers of pre‐hospital delay in patients with diabetic foot: A cross‐sectional survey - Huiwen Xu; Chen Wu; Shengxiao Xiang; Shuang Qiu; Yan Chen; En Takashi; Kiyoko Yanagihara; Ping Xie (Wiley, 2024)
Abstract Aim This study aimed to determine the psychosocial markers associated with pre‐hospital delay among patients with diabetic foot (DF). Design This study has a cross‐sectional design. Methods The participants completed a questionnaire including pre‐hospital time, demographic characteristics, Social Support Rate Scale, Brief Illness Perception Questionnaire and Type D Personality Scale‐14. Bivariate and multivariate analyses were conducted to explore independent associations with pre‐hospital delay. Results Only 1.8% (3/164) of participants arrived at the hospital for medical care in 24 h of symptom onset. Patients with low utilization of social support (p = 0.029), low negative illness perceptions (p = 0.014) and high levels of negative affectivity (p = 0.009) are likely to arrive late at the clinic. Medical staff should pay attention to identifying diabetic patients' Type D personalities and take actions to improve their social support as well as illness perception, so as to reduce the occurrence of hospital delay. Implications for the Profession and/or Patient Care Psychosocial factors play a vital role in the delay in seeking medical treatment for patients with DF. Medical staff need to improve patients' illness perception as well as self‐management ability through health education. Importantly, key family members provide an emotional and psychological support system for diabetic patients. Therefore, nurses need to work with family members together to give information and psychological support during family visits. Additionally, building and maintaining trust with patients is crucial to encouraging individuals to express their concerns and worries. In this case, nurses may identify patients' negative emotions and conduct timely intervention, so as to achieve favourable outcomes. Patient or Public Contribution This study used a convenience sample of 164 participants with DF recruited from the wound clinic of Northern Jiangsu People's Hospital and Yangzhou Hospital of TCM in China.